Sulfur-encapsulated zeolite micromotors for the selective removal of cesium from high-salt water with accelerated cleanup times. (August 2021) - Lee, Yeonsoo; Park, Chan Woo; Kim, Hyung Ju; Kim, Sung-Jun; Lee, Taek Seung; Yang, Hee-Man
Abstract: Bubble-propelled sulfur-encapsulated NaX zeolite (S-NaX) micromotors were developed for the selective removal of cesium from high-salt conditions with accelerated cleanup times. NaX was first modified with sulfur to provide additional Lewis acid−base interactions with Cs + for enhanced Cs + selectivity, and then Pt was half-deposited on S-NaX for bubble propulsion via the catalytic decomposition of H2 O2 . The average velocity of the resulting S-NaX/Pt micromotors in 5 wt% H2 O2 is 39.7 ± 17.1 μm/s, which is higher than that of a previously reported Cs adsorbent micromotor (35.4 μm/s). The Cs + ion-exchange kinetics of the S-NaX micromotor is 1.32 times higher than that of the NaX micromotor in a 5 wt% H2 O2 solution where the molar ratio of Na + to Cs + is 200, even though the sulfur in the S-NaX micromotor causes an adverse effect on the propulsion speed due to the sulfur poisoning effect. Moreover, the S-NaX micromotor in simulated groundwater also exhibited excellent Cs + removal performance with distribution coefficient (Kd ) values at least 3.2 times higher than those of the nonpropelled S-NaX and NaX micromotor, demonstrating the great potential for the treatment of radioactive Cs + -contaminated water. Graphical abstract: Image 1 Highlights: Selective removal of cesium using a zeolite micromotor was first developed. The bubble-propelled NaX micromotor significantly reduced the Cs + cleanup time. A sulfur-encapsulated NaX micromotor is effective for the selective removal of cesium. The sulfur-encapsulated zeolite micromotor shows the highest Cs + removal performance from groundwater.